1996
DOI: 10.1677/joe.0.1500265
|View full text |Cite
|
Sign up to set email alerts
|

Pituitary and ovarian expression of the endogenous follicle-stimulating hormone (FSH) subunit genes and an FSH β-subunit promoter-driven herpes simplex virus thymidine kinase gene in transgenic mice; specific partial ablation of FSH-producing cells by antiherpes treatment

Abstract: The ovarian expression of the endogenous follicle-stimulating hormone beta-subunit (FSH beta) and common alpha-subunit (C alpha) genes, and a herpes simplex virus thymidine kinase (tk) transgene, driven by a 2.3 kb bovine FSH beta promoter, was studied in normal and transgenic (tg) mice, tk functions not only as a neutral reporter that enables the study of the promoter function but also as an exogenously inducible toxigene. Reverse transcription-PCR followed by Southern blot hybridization with a nested probe w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
7
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 24 publications
3
7
0
Order By: Relevance
“…Similarly, earlier efforts failed to detect expression of gonadotropin alpha subunit in ovine ovaries (A.S. McNeilly, unpublished results). In contrast, consistent with the present results in horses, the gonadotropin alpha subunit has reportedly been detected by microarray analyses of human follicular cells [53], and others have reported the presence of gonadotropin alpha and FSH beta subunits in ovarian luteal and interstitial cells of normal adult mice [72]. In the present study, we also sought to determine the presence of gonadotropin beta subunits in equine follicular cells using qPCR.…”
Section: Donadeu Et Alsupporting
confidence: 89%
“…Similarly, earlier efforts failed to detect expression of gonadotropin alpha subunit in ovine ovaries (A.S. McNeilly, unpublished results). In contrast, consistent with the present results in horses, the gonadotropin alpha subunit has reportedly been detected by microarray analyses of human follicular cells [53], and others have reported the presence of gonadotropin alpha and FSH beta subunits in ovarian luteal and interstitial cells of normal adult mice [72]. In the present study, we also sought to determine the presence of gonadotropin beta subunits in equine follicular cells using qPCR.…”
Section: Donadeu Et Alsupporting
confidence: 89%
“…1). These findings also are supported by mammalian investigations that demonstrated FSH expression in both ovary [37] and testis [38]. Although evidence exists for the expression of both Cg␣ and LH␤ in the rat testis [39], no corresponding reports, to our knowledge, have appeared for LH␤ expression in the mammalian ovary.…”
Section: Presence Of Uniquely Expressed Genes In Salmon Ovary and Testissupporting
confidence: 72%
“…Previous investigators [21,22] have also reported ectopic expression of the FSHβ subunit and/or HSV-TK gene in tissues other than the pituitary in mice. But in this study, as previously described, we did not detect the transcripts of the FSHβ subunit in the rat gonads (the testis and ovary).…”
Section: Discussionmentioning
confidence: 98%